2022
DOI: 10.1155/2022/8442734
|View full text |Cite
|
Sign up to set email alerts
|

Hyssopus Essential Oil: An Update of Its Phytochemistry, Biological Activities, and Safety Profile

Abstract: The genus Hyssopus is widespread in central Asia, East Mediterranean, and Mongolian areas. It has six main species which are used as herbal remedies, such as Hyssopus officinalis which is used as a condiment and flavoring agent in food industry. The other five species are H. ambiguus, H. cuspidatus, H. latilabiatus, H. macranthus, and H. seravschanicus. Its species are used in the treatment of various ailments such as cold, cough, loss of appetite, fungal infection, and spasmodic condition. Its constituents es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 59 publications
(72 reference statements)
0
20
0
Order By: Relevance
“…There is proof that the usage of natural compounds originating from microbes, animals, or plants for medical purposes goes back to the Neanderthal epoch [114,115]. People have gathered knowledge and become an expert in their applications due to various biological activities of isolated natural items [116][117][118]. The invention of the chemical structure aided the manufacturing of the essential compounds rather than separating them from natural sources [119].…”
Section: Discussionmentioning
confidence: 99%
“…There is proof that the usage of natural compounds originating from microbes, animals, or plants for medical purposes goes back to the Neanderthal epoch [114,115]. People have gathered knowledge and become an expert in their applications due to various biological activities of isolated natural items [116][117][118]. The invention of the chemical structure aided the manufacturing of the essential compounds rather than separating them from natural sources [119].…”
Section: Discussionmentioning
confidence: 99%
“…Also, they have traditionally been used as a muscle pain reliever, tonic, and carminative agents to treat stomach and intestinal disorders such as cramps, nausea, indigestion, and diarrhea ( Tepe and Cilkiz, 2016 ). In addition, Hyssopus officinalis is used for the treatment of cough, cold, loss of appetite, fungal infection, and spasmodic conditions ( Sharifi-Rad et al, 2022 ), while Ziziphora clinopodioides is known as stomachic, carminative, and wound healing herb ( Ozturk and Ercisli, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deciphering the mechanisms of multidrug resistance could contribute to the efficiency of therapeutic strategies for the treatment of neoplastic diseases, and also mitigate the side effects of drugs. [ 8 , 165 ]. The reason for this is the increased activity of ATP-binding cassette family transporters (ABC) [ 166 ].…”
Section: Quercetin As Bioactive Molecule In Cancermentioning
confidence: 99%
“…Chemopreventive properties of natural bioactive substances have been increasingly important to researchers in the field of medicine in recent years [5,6]. More and more research has demonstrated the anti-cancer potential and usefulness of natural ingredients in the treatment of cancer [7][8][9][10]. Quercetin, a plant flavonol produced from the polyphenol family, is…”
Section: Introductionmentioning
confidence: 99%